2009
DOI: 10.1097/ajp.0b013e31819655b3
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Mechanical Pain Sensitivity Over Nerve Tissues in Patients With Strictly Unilateral Migraine

Abstract: In patients with unilateral migraine, we found increased mechano-sensitivity of the supra-orbital nerve on the symptomatic side of the head. Outside the head, the same patients showed increased mechano-sensitivity of the main peripheral nerves of both upper limbs, without asymmetries. Such diffuse hypersensitivity of the peripheral nerves lends further evidence to the presence of a state of hyperexcitability of the central nervous system in patients with unilateral migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…This relationship is consistent with the clinical impression of a tendency towards an anatomical spreading of pain with time but has to be confirmed in future prospective studies. Also other studies have shown widespread hyperalgesia in a wide range of chronic pain conditions, including WAD [8,9,18,21], fibromyalgia [19,21,69,70], tension-type headache [16,71], idiopathic neck pain [17], epicondylalgia [14], pelvic pain syndrome [15], and low-back pain [13,72]. Based on studies of chronic WAD [6,9,68,73-76] we recently concluded, that widespread hypersensitivity of pressure can be present without widespread clinical pain [77], which is in agreement with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is consistent with the clinical impression of a tendency towards an anatomical spreading of pain with time but has to be confirmed in future prospective studies. Also other studies have shown widespread hyperalgesia in a wide range of chronic pain conditions, including WAD [8,9,18,21], fibromyalgia [19,21,69,70], tension-type headache [16,71], idiopathic neck pain [17], epicondylalgia [14], pelvic pain syndrome [15], and low-back pain [13,72]. Based on studies of chronic WAD [6,9,68,73-76] we recently concluded, that widespread hypersensitivity of pressure can be present without widespread clinical pain [77], which is in agreement with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…24 Sensitization mechanisms have been examined by assessing pressure pain thresholds (PPT) over nerve trunks in patients with whiplash-associated disorders, 57,59 mechanical neck pain, 51 chronic tension type headache, 26 or migraine. 25 Generalized sensitization identified by lower PPT over the median, radial, and ulnar nerve trunks has been found in patients with whiplash 57,59 and unilateral migraine, 25 suggesting possible hyperexcitability of the central nervous system. 34 It has also been shown that patients with unilateral LE 23 and unilateral CTS 28 exhibited signs of central hyperexcitability as demonstrated by lower PPT over the median, ulnar, and radial nerve trunks bilaterally when compared to healthy controls.…”
Section: Participants P Atients Diagnosed With Cts Bymentioning
confidence: 99%
“…The frequency of migraine attacks and the duration of the disorder did not correlate with the number of painful arteries in our migraineurs, while Calandre et al [5] did find such correlation in relation to the number of muscle trigger points, and Fernandez-de-las-Peñas et al [13] found a negative correlation with pressure pain threshold in the supraorbital nerve. Our data suggest that arterial pain is often inherent in migraine, while attack frequency and duration of the disorder are regulated by other factors, most probably hypersensitivity of pain-regulating centers.…”
Section: Discussionmentioning
confidence: 77%
“…Many studies have evaluated pressurepain threshold or tenderness or trigger points in pericranial muscles [1][2][3][4][5][6][7][8] and nerves [13]. Surprisingly, the most frequent ''trigger'' (not only ''tender'') points detected by Calandre et al [5] are located in the same areas (''anterior temporal'' in 42.6% and ''suboccipital'' in 33.4%) of the arteries we found to be most frequently painful.…”
Section: Discussionmentioning
confidence: 81%